ZnO Based Resistive Random Access Memory Device: A Prospective Multifunctional Next-Generation Memory - Isyaku, U.B. (Institute of Electrical and Electronics Engineers Inc., 2021)
Numerous works that have demonstrated the study and enhancement of switching properties of ZnO-based RRAM devices are discussed. Several native point defects that have a direct or indirect effect on ZnO are discussed. The use of doping elements, multi-layered structures, suitable bottom and top electrodes, controlling the deposition materials, and the impact of hybrid structure for enhancing the switching dynamics are discussed. The potentials of ZnO-based RRAM for invisible and bendable devices are also covered. ZnO-based RRAM has the potential for possible application in bio-inspired cognitive computational systems. Thus, the synapse capability of ZnO is presented. The sneak-path current issue also besets ZnO-based RRAM crossbar array architecture. Hence, various attempts to subdue the bottleneck have been shown and discussed in this article. Interestingly, ZnO provides not only helpful memory features. However, it demonstrates the ability to be used in nonvolatile multifunctional memory devices. Also, this review covers various issues like the effect of electrodes, interfacial layers, proper switching layers, appropriate fabrication techniques, and proper annealing settings. These may offer a valuable understanding of the study and development of ZnO-based RRAM and should be an avenue for overcoming RRAM challenges. Â© 2013 IEEE.